THE RELATIONSHIP BETWEEN EMOTIONAL MATURITY AND FORGIVENESS AMONG STUDENTS AT STATE JUNIOR HIGH SCHOOL 19 IN MEDAN - Putri Agustina Sinaga; Veronica Veronica; Verlin Verlin; Viora Lie (Jurnal Konseling Pendidikan Islam, 2026)
This study aimed to examine the relationship between emotional maturity and forgiveness among students of SMP Negeri 19 Medan. The research employed a quantitative approach using a correlational method. The sample consisted of 146 students selected through disproportionate stratified random sampling. The research instruments included two scales, namely the emotional maturity scale and the forgiveness scale, both of which had been tested for validity and reliability prior to data collection. Data were analyzed using the Pearson Product Moment correlation technique. The results revealed a highly significant positive relationship between emotional maturity and forgiveness, with a correlation coefficient of r = 0.773 and a significance value of p = 0.000 (p < 0.05). These findings indicate that higher levels of emotional maturity are associated with higher levels of forgiveness among students. Furthermore, emotional maturity contributed effectively 59.8% to forgiveness, while the remaining 40.2% was influenced by other factors beyond the scope of this study. These findings emphasize the importance of emotional maturity as a contributing factor in supporting forgiveness among adolescents in the school environment.